PENGARUH KUALITAS PRODUK, PROMOSI DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN SEPATU SEPAKBOLA MEREK SPECS DI KOTA PANGKALPINANG - Rizal Rizal; Afizal Afrizal; Juhari Juhari (JEM Jurnal Ekonomi dan Manajemen, 2020)
This study aims to determine the effect of product quality, promotion, and brand image on purchasing decisions of Specs brand soccer shoes in Pangkal Pinang City. Respondents in this study were consumers of Specs brand soccer shoes, totaling 40 people. The sampling technique is a non-probability sampling technique, namely accidental sampling. data were collected by distributing questionnaires. Data were analyzed by multiple linear regression analysis. The results showed that product quality, promotion, and brand image simultaneously affect purchasing decisions. Specifications of branded soccer shoes in Pangkalpinang City. Product quality, promotion, and brand image partially have a positive effect on purchasing decisions for Specs brand soccer shoes in Pangkalpinang City.